Gendered economic policy making: The case of public expenditures on family allowances - Oznur Ozdamar (Kiel Institute for the World Economy (IfW), 2015)
Parliament is the place where politicians make laws to set the policy direction of countries. Non-involvement of different voices such as gender, race and ethnicity in policy decisions may create an inequality in policy-making. Regarding gender, previous literature suggests that women and men may have different policy preferences and women give more priority to policies related to their traditional roles as care givers to children in the family. Public spending on family allowances is one of the economic policies that plays an important role in helping families for the childcare. This paper contributes to the literature by analyzing the relationship between female political representation and public spending on family allowances as well as within a perspective of critical-mass framework. Overall findings support the fact that when the fraction of female politicians is above a certain critical-mass threshold, there is a significantly different allocation of public spending on family allowances.
Keywords: H53; H83; J16; 330; women in economic policy-making; public expenditures on family allowances; critical mass; panel data analysis